Powder metallurgical materials and products. Methods of testing and chemical analysis of hardmetals. Chemical analysis by flameatomic absorption spectrometry. Determination of molybdenum, titanium and vanadium in contents from 0.01% to 0.5% (7Im/m7R) Part 4.17.4, (30th June 1986) - British Standards Institution,
No abstract available